Anwar on trial in the face of injustice - Pawancheek Marican (Gerakbudaya Enterprise, 2009)
The Anwar Ibrahim trial during the late Nineties left the landscape of Malaysia's judiciary forever changed. Convicted to a six year prison term that many believe to have been trumped up, Anwar has become the symbol of a new generation of Malaysians determined to seek truth and justice. With his second trial nearing the point of conclusion and Anwar facing another jail sentence on what many believe to be a second round of politically motivated charges as a result of his insurgent political campaign, this book offers important historical context to the case. Anwar On Trial gives readers a cogent look into the detailed workings of the 1998 corruption trial of Anwar Ibrahim. Captured through the lens of a lawyer who was present throughout the proceedings, this book presents a first-hand account of the goings-on in court and outside of it. Pawancheek Marican examines the way that the Malaysian judiciary was systematically emasculated and turned into a pawn of the executive, the consequences of which will linger for many generations. From the trial judge who forbade Anwar to argue his defense of conspiracy to the abuse of the Attorney-General's chambers, this book lays bare the political machinations taking place behind the scenes by those in power to remain in power. The information contained within this book comes at opportune moment as Anwar Ibrahim faces yet another sodomy trial in 2009, this time, however from the freedom of his own home and as the Opposition Leader and Member of Parliament for Permatang Pauh in Penang.